Supporting Information System Integration Decisions in the Post-Merger Context - Ksenija Lace (Complex Systems Informatics and Modeling Quarterly)
Consolidation of organizations and assets through Mergers and Acquisitions (M&A) is one of the strategies for organizational growth. However, despite the big popularity, the results of M&A initiatives are questionable. The main idea behind M&A is to create a new organization by combining several existing organizations. This new organization is created through a transformation process often called a post-merger. A significant part of the post-merger process is the integration of information systems. The success of post-merger information systems integration is the result of successful integration decisions. This study focuses on the problem of how a novice organization in post-merger initiatives can handle complexity in the decision-making process of post-merger information systems integration with its internal resources, without involvement of an external expertise, but with a support method to compensate the lack of expertise for informed decision-making. The extended decision-making process can be divided into three phases – identification of necessary decisions, decision-making, and decision implementation. This study focuses on the first two phases. For each of the phases, a specialized sub-method was developed, focused, respectively, on the identification of necessary decisions (AMILI) and decision-making as a choice between possible integration options (AMILP). Supporting tools were also developed for each of the sub-methods.